2020
DOI: 10.5194/jsss-9-51-2020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the single point uncertainty of customized polymer gear wheels using structured-light scanning with various polygonization settings

Abstract: Abstract. During the manufacturing of work pieces, geometrical deviations from the intended nominal geometry of the designer are inevitable. The procedure of conformance testing defined in ISO 14253-1:2018-07 is used to ensure the function of a work piece by verifying the geometrical compliance with pre-defined tolerance specifications. Depending on the measurement setup used for the validation step, it is possible that the local measurement uncertainty is too large in order to provide a meaningful conformance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Another issue worth mentioning in relation to the literature survey conducted concerns advanced measurement and analysis techniques. In this direction, studies by [ 28 , 29 ] have been identified that follow advanced measuring techniques in polymer machining [ 30 , 31 , 32 , 33 ], dealing with the issue of coordinate measuring machines (CMM) for polymers, while [ 34 , 35 ] address the topic of artificial vision systems for machined parts, and [ 36 , 37 , 38 , 39 , 40 ] discuss precision and accuracy in polymer drilling. All of these papers explore state-of-the-art equipment and use software in the accurate measurement of machined-part features, with a focus on coordinate measuring machines and machine vision systems.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue worth mentioning in relation to the literature survey conducted concerns advanced measurement and analysis techniques. In this direction, studies by [ 28 , 29 ] have been identified that follow advanced measuring techniques in polymer machining [ 30 , 31 , 32 , 33 ], dealing with the issue of coordinate measuring machines (CMM) for polymers, while [ 34 , 35 ] address the topic of artificial vision systems for machined parts, and [ 36 , 37 , 38 , 39 , 40 ] discuss precision and accuracy in polymer drilling. All of these papers explore state-of-the-art equipment and use software in the accurate measurement of machined-part features, with a focus on coordinate measuring machines and machine vision systems.…”
Section: Introductionmentioning
confidence: 99%